Apakah Rusia Menggunakan Strategi Hedging Di Kawasan Timur Tengah? - Dwi Arif Wicaksono (Jurnal Studi Diplomasi dan Keamanan, 2016)
Russian foreign policy in Middle East has been deemed as balancing towards the US and its allies. Following ‘the Arab Spring” in Middle East Russia began to strengthen its presence in the region, mainly through its support to Assad regime in Syria. Instead of balancing, this paper employs strategic hedging in analysing Russia’s strategy in the Middle East against the US domination in the region. This paper argues that Russia’s hegding mainly conducted through indirect (soft) balancing, follows by other components of hedging. Among the weakest component of Russia’s hedging is economic pragmatism.